Numerical and modelling studies of the geogrid-reinforced ash-storage embankment in the conditions of the undermined territories - Rauan E. Lukpanov (Journal of Water and Land Development)
The article presents the results of the study of the stability of the reinforced ash-storage embankment (ASE) of a functioning metallurgical plant. The purpose of the tests was to determine the numerical modelling correction factors based on the model test results. The model tests were performed at a scale of 1:30 to the full-scale embankment. The numerical modelling was a simulation of model testing in two tasks. The first task considered the simulation of model testing on a reduced scale (relative to ASE) of a real sheet, using the characteristics of an equivalent material. The second task considered the simulation of ash-and-slag mixtures on an in situ scale with real characteristics but under the conditions of the model tests. The quantitative assessment of each of the research methods, as well as the identified regularities of the stress–strain states of reinforced and unreinforced embankment, are presented in the article. Based on the results of the studies, a method of stability assessment by numerical modelling was obtained, the results of which reflect the most reliable condition of the stress-strain state of the reinforced embankment (since the results are subject to adjustment based on the regularities of the model, although still in situ tests).